2013
DOI: 10.5296/jsr.v4i2.4847
|View full text |Cite
|
Sign up to set email alerts
|

Public Spending on Transport Infrastructure and Economic Growth in Nigeria, 1981-2010

Abstract: Transport remains one of the major infrastructural facilities critical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…The study revealed that government expenditures on education, transport and communication, and health have positive but insignificant impact on economic growth in Nigeria. Amadi et al (2013) examined the effect of public spending on transport infrastructure and economic growth in Nigeria from the period 1981 to 2010. The study employed an ordinary least squares method to analyze the impact and the results show that public spending on transport infrastructure has a negative and insignificant impact on economic growth in Nigeria.…”
Section: Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed that government expenditures on education, transport and communication, and health have positive but insignificant impact on economic growth in Nigeria. Amadi et al (2013) examined the effect of public spending on transport infrastructure and economic growth in Nigeria from the period 1981 to 2010. The study employed an ordinary least squares method to analyze the impact and the results show that public spending on transport infrastructure has a negative and insignificant impact on economic growth in Nigeria.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Furthermore, while a lot of empirical works abound on the relationship between transport and communication and economic growth across the globe, there exist mixed findings. For example, the studies of scholars like Narayan (2021), Barilee and Benvolio (2021), and Omokaro and Ikpere (2019) found a positive and significant relationships between transport and communication expenditure and economic growth, whereas Charles et al (2018), andAmadi et al (2013) established negative impact of government expenditure and economic growth in Nigeria. It is against this backdrop that this study attempts to examine the impact of transport and communication capital expenditure on economic growth in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…langsung. Menurut temuan Chukwuemeka et al (2013) di Nigeria, sektor transportasi memiliki hubungan yang negatif dan tidak signifikan karena anggaran di sektor tersebut. Untuk itu perlu dipastikan bahwa dana yang bersumber dari belanja pemerintah memang untuk sektor transportasi, dan adanya pengawasan terhadap dana yang telah dialokasikan.…”
Section: Pengeluaran Pemerintah Sektor Transportasiunclassified
“…However, few argued otherwise. The strand of these studies includes Al Nasser (2007), Chukwuemeka et al (2013), Mohmand et al (2017), Ogwo and Godswill (2017), Shi et al (2017), andSoneta et al (2012). Most of the studies mentioned above looked at the role of infrastructure stock in economic development, emphasizing the importance of efficient and better infrastructure utilization.…”
Section: Introductionmentioning
confidence: 99%